Effectiveness Of Joint Patrol For National Marine Security And Safety To Minimize Illegal Goods Activities In Batam City - Siti Sarah; Surya Wiranto; Herlina Juni Risma Saragih; Pujo Widodo; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
Smuggling is an important problem in many Indonesian maritime areas, including in Batam City. Illegal goods smuggling is one of the problems that until now has a high intensity in several Batam ports. The prevention and handling measures taken by the government have been very strict and almost every day Beacukai Batam takes action, but smuggling violations still occur every year. This may be influenced by the behavior of the people living in the area around the port, not only as smugglers but also as users and consumers so the demand for illegal goods continues to increase. This study aims to find out whether the joint patrols that have just been implemented in 2022 can minimize illegal goods smuggling activities in Batam City. The method used is a qualitative approach with interviews and literature studies. At the fisrt, it was feared that the joint patrols carried out by several agencies related to maritime security would cause overlapping interests or the possibility of sectoral egos, but in reality the patrols ran smoothly and according to the expected plan. Joint patrols are considered by several agencies related to maritime security to have an influence in reducing the number of smuggling of illegal goods and the number of violations in the standard of transporting goods by ship.